Intra-articular injection of photo-activated platelet-rich plasma in patients with knee osteoarthritis: a double-blind, randomized controlled pilot study. Issue 1 (December 2016) - Paterson, Kade; Nicholls, Melissa; Bennell, Kim; Bates, Dan
Abstract Background Improvements in knee osteoarthritis (OA) symptoms with platelet-rich plasma (PRP) have been attributed to its ability to modify intra-articular inflammatory processes. Photo-activation of peripheral blood also improves inflammatory mediators associated with OA, however combined photo-activated PRP (PA-PRP) has not been investigated. This pilot study assessed the feasibility, safety and symptomatic and functional change following injections of PA-PRP compared to hyaluronic acid (HA) in people with knee osteoarthritis (OA). Methods Thirty seven people with knee OA were enrolled in this double-blind randomized controlled pilot study set in a sports medicine clinic. Participants were randomly allocated to receive three injections of either PA-PRP or HA. The patients and the administering doctor were blinded to group allocation. Outcomes included recruitment and safety data, 100 mm visual analogue pain score (VAS), the Knee Osteoarthritis Outcome Score (KOOS), Knee Quality of Life (KQoL) scale, maximum hopping distance and number of knee bends in 30 s at four and 12 weeks. Results Twenty three (62 %) participants met the inclusion criteria, of which 12 (32 %) were randomized to the PA-PRP group and 11 (30 %) to the HA group. Two participants did not complete the intervention and two withdrew following their first assessment. Minor pain and swelling during the injection period was reported by two participants from the PA-PRP group. The PA-PRP group demonstrated significant improvements in the VAS (p < 0.01, ETA = 0.686), KOOS Pain (p < 0.05, ETA = 0.624), KQoL Physical (p < 0.05, ETA = 0.706) and KQoL Emotional subscales (p < 0.05, ETA = 0.715) at four and 12 weeks. The PA-PRP group also significantly improved hoping (p < 0.05, ETA = 0.799) and knee bends (p < 0.01, ETA = 0.756) at four or 12 weeks. The HA group showed improvements on only the KOOS Function subscale at 12 weeks (p < 0.01, ETA = 0.602). After controlling for baseline values, there were no significant between-group differences at either time-point. Conclusions This study provides proof-of-concept evidence concerning the feasibility and safety of PA-PRP injections necessary to inform a larger clinical trial in people with knee OA. Our preliminary results also suggest PA-PRP improves self-reported pain, symptoms and lower extremity function, however no between-group differences were found. Photo-activated PRP may provide a safe and effective novel treatment for knee OA. Trial registration ACTRN12611000651987